Investigating the effects of knowledge management and organizational innovation on organizational strategy: Evidence from insurance industry - Seyed Mohsen Taheri; Amir Homayoun Sarfaraz; Seyed Mohsen Seyed AliAkbar (Management Science Letters)
This paper presents an exploratory factor analysis on knowledge management and organizational innovation items influencing on organizational strategy. The study designs a questionnaire in Likert scale and distributes it among 210 employees in an insurance firm named Dana located in Iran. Cronbach alpha has been well above 0.90, which confirms the validity of the overall survey. Using principle component analysis, the study extracts six critical success factors influencing on knowledge management including knowledge management processes, organizational culture, organizational structure, human resources, information technology, top management support and three factors of innovation including product innovation, process innovation, and organizational performance.